Bangladesh Krira Shikka Protishtan (BKSP) Chittagong, Bangladesh - Hasan, S. M. Zahid (BRAC University, 2014)
This thesis submitted in partial fulfillment of the requirement for the degree of Bachelor of Architecture in Architecture, 2014.